Soil gas radon and soil permeability assessment: Mapping radon risk areas in Perak State, Malaysia. - Habila Nuhu (Public Library of Science (PLoS), 2021)
In this study geogenic radon potential (GRP) mapping was carried out on the bases of field radon in soil gas concentration and soil gas permeability measurements by considering the corresponding geological formations. The spatial pattern of soil gas radon concentration, soil permeability, and GRP and the relationship between geological formations and these parameters was studied by performing detailed spatial analysis. The radon activity concentration in soil gas ranged from 0.11 to 434.5 kBq m-3 with a mean of 18.96 kBq m-3, and a standard deviation was 55.38 kBq m-3. The soil gas permeability ranged from 5.2×10-14 to 5.2×10-12 m2, with a mean of 5.65×10-13 m2. The GRP values were computed from the 222Rn activity concentration and soil gas permeability data. The range of GRP values was from 0.04 to 154.08. Locations on igneous granite rock geology were characterized by higher soil radon gas activity and higher GRP, making them radon-prone areas according to international standards. The other study locations fall between the low to medium risk, except for areas with high soil permeability, which are not internationally classified as radon prone. A GRP map was created displaying radon-prone areas for the study location using Kriging/Cokriging, based on in situ and predicted measured values. The GRP map assists in human health risk assessment and risk reduction since it indicates the potential of the source of radon and can serve as a vital tool for radon combat planning.